Pola Adaptasi Ekologi Budaya Tiga Komunitas di Jambi - Nana Kristiawan (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2017)
Abstract: Pattern of cultural ecological adaptation of the three group of society in Jambi is considered diverse. The background of this study is the occurrence of traditional cultifation practice, known as shifting cultivation, in Jambi. The first purpose of this study is to analyze pattern of adaptation of Talang Mamak, Malay and Javanese community by the existence of industrial economy of rubber plantation. Secondly, this study aims to analyze economic stability in livelihood system of the three community groups. This research use qualitative and quantitative methods. Data collection technique use in-depth interview, observation and survey of livelihood system. The results show that adaptation of cultural ecology of Talang Mamak and Java , even though based on forest ecosystem, but Talang Mamak shows the pattern of hunting and gathering. On the other hand, migrants from Java worked in the forest as loggers. The differences of adaptation method from each community show the process to achieve different stability of livelihood. Livelihood stability of Malay migrants is better than the other two, shown by incomes and degree of resilience that considered as better than the other groups. This condition caused by the adaptability of the households to the environment is higher, specifically on the range of available jobsAbstrak: Pola adaptasi ekologi budaya ketiga komunitas menunjukkan keragaman dalam proses pencarian penghidupan. Penelitian ini dilatarbelakangi oleh adanya budidaya tanam pertanian tradisional atau pertanian ladang berpindah. Tujuan penelitian ini adalah Pertama, untuk menganalisis pola adaptasi komunitas Talang Mamak, komunitas Melayu dan Pendatang Jawa terhadap sistem ekonomi industrial perkebunan karet. Kedua, Untuk menganalisis tentang stabilitas ekonomi dalam sistem mata pencaharian tiga komunitas. Penelitian menggunakan metode penelitian kualitatif dan kuantitatif. Teknik pengumpulan data yang digunakan adalah melalui wawancara mendalam, observasi dan survey tentang sistem penghidupan tiga komunitas. Hasilnya menunjukkan bahwa adaptasi ekologi budaya dari Talang Mamak dan Pendatang Jawa sekalipun berbasis pada ekosistem hutan, namun Talang Mamak menunjukkan cara bernafkah hunting and gathering. Di lain pihak, Pendatang Jawa bekerja di hutan sebagai pembalak kayu. Perbedaan cara beradapatasi dari tiap kelompok masyarakat menunjukkan proses menuju kestabilan nafkah yang berbeda. Stabilitas ekonomi rumahtangga Pendatang Melayu dilihat dari struktur pendapatan dan tingkat kelentingannya jauh lebih baik dibandingkan dua kelompok masyarakat yang lain. Hal ini karena daya adaptasi rumah tangga tersebut terhadap lingkungan lebih tinggi terutama dalam ragam pekerjaan yang lebih banyak.